Dose‐finding and efficacy confirmation trial of the superselective intra‐arterial infusion of cisplatin and concomitant radiotherapy for locally advanced maxillary sinus cancer (Japan Clinical Oncology Group 1212): Dose‐finding phase. Issue 3 (11th November 2017) - Homma, Akihiro; Onimaru, Rikiya; Matsuura, Kazuto; Shinomiya, Hirotaka; Sakashita, Tomohiro; Shiga, Kiyoto; Tachibana, Hiroyuki; Nakamura, Kenichi; Mizusawa, Junki; Kitahara, Hideaki; Eba, Junko; Fukuda, Haruhiko; et al.
Abstract: Background: We are currently undertaking a multi‐institutional prospective trial of the superselective intra‐arterial infusion of high‐dose cisplatin with concomitant radiotherapy for patients with T4aN0M0 or T4bN0M0 locally advanced maxillary sinus squamous cell carcinomas (SCC). We herein report the results of the dose‐finding phase. Methods: The dose‐finding phase sought to evaluate the incidence of dose‐limiting toxicities and determine the recommended number of cycles of the intra‐arterial infusion of cisplatin. In this phase, 100 mg/m 2 of cisplatin was administered intra‐arterially weekly for 7 weeks with concomitant radiotherapy (70 Gy). Results: All 18 patients received a full dose of radiotherapy. The number of cycles of cisplatin was 7 in 13 patients and 6 in 5 patients. The dose‐limiting toxicities were observed in 5 patients. Conclusion: These results indicated that this therapy is safe and well‐tolerated at 7 cycles of cisplatin, which was determined to be the recommended number of cycles for locally advanced maxillary sinus SCC.